Apostlen og geniet: : Romerbrevets kærlighedsbegreb i Kjerlighedens Gjerninger - Haagerup, Anders (Dansk Teologisk Tidsskrift, 2024)
This article seeks to explore the concept of love in Romans in order to examine whether Kierkegaard operates with a similar concept in his Works of Love. It argues, first, that Paul creates an understanding of agapeic love centred around Rom 10,4 and Rom 13,8-10. A chiastic development of the concept of love sees the love of God being the end(goal) of the law which allows the love of humans to fulfil the law. The second part of the article outlines the Pauline traits in Kierkegaard’s concept of love in Works of Love. Here it is shown how Kierkegaard appropriates Paul’s chiastic approach to love as well as the understanding of love as sustaining a Christian identity of minority. Finally, the article acknowledges the differences between Paul, the apostle, and Kierkegaard, the genius, while also accentuating the similarities in their radical proposals of Christian love.